2022
DOI: 10.1111/cts.13209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food on capsule and granule formulations of selumetinib

Abstract: Selumetinib is an oral, potent, and highly selective allosteric MEK1/2 inhibitor approved for the treatment of pediatric patients (aged ≥2 years) with neurofibromatosis type 1 who have symptomatic, inoperable plexiform neurofibromas. A granule formulation of selumetinib is under development to improve dosing precision for younger pediatric patients who may be unable to swallow capsules. This phase I crossover study investigated the effect of food on the pharmacokinetic (PK) properties of selumetinib capsule an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 15 publications
(66 reference statements)
1
11
1
Order By: Relevance
“…Dermatitis acneiform was the most commonly reported non-GI AE, and this AE has also been frequently reported in previous selumetinib studies. 11 , 16 , 18 , 29 No new safety signals for selumetinib were identified; the AEs reported were similar in both the fed and fasted treatment periods and were comparable to previous studies. 11 , 17 …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Dermatitis acneiform was the most commonly reported non-GI AE, and this AE has also been frequently reported in previous selumetinib studies. 11 , 16 , 18 , 29 No new safety signals for selumetinib were identified; the AEs reported were similar in both the fed and fasted treatment periods and were comparable to previous studies. 11 , 17 …”
Section: Discussionsupporting
confidence: 82%
“… 17 A further study conducted in healthy adults showed that consumption of a low-fat, low-calorie meal reduced both the rate and extent of absorption after a single dose of selumetinib; C max was reduced by 60%, T max was delayed by 2.5 h, and AUC was reduced by 38%. 18 Therefore, administration in the fed rather than the fasted state could affect exposure to, and absorption of, selumetinib.…”
mentioning
confidence: 99%
“…23,24 Data from 3 previous phase 1, single-dose, foodeffect PK studies have indicated that administration with a meal may reduce selumetinib absorption compared with administration during a fasted state. 12,13,25 Specifically, a study conducted in healthy male adults (D1532C00069) demonstrated that consumption of a high-fat meal reduced the rate of absorption of selumetinib, as demonstrated by a 50% reduction in maximum concentration (C max ) and a 1.5-hour delay in time to reach C max (T max ), but did not cause a clinically relevant reduction in the extent of absorption of selumetinib (area under the concentration-time curve [AUC] was reduced by 16%), versus administration under fasted conditions. 13 Similar findings were reported in another study (D1532C00020) in which adults with advanced solid tumors were administered selumetinib with a high-fat meal (C max was reduced by 62%, T max was delayed by 2.5 hours, and AUC was reduced by 19% versus administration under fasted conditions).…”
mentioning
confidence: 99%
“…12 In study D1532C00089, which was conducted in healthy adults, administration of a single dose of selumetinib after a low-fat meal reduced the rate of absorption, as demonstrated by a 60% reduction in C max and a 2.5-hour delay in T max , and the extent of absorption, as demonstrated by a 38% reduction in AUC. 25 Therefore, further investigations are warranted to assess whether the current recommended dose of selumetinib can maintain an acceptable efficacy and safety profile if taken with food.…”
mentioning
confidence: 99%
See 1 more Smart Citation